RDM1 promotes neuroblastoma growth through the RAS–Raf–MEK–ERK pathway. Issue 3 (28th January 2019) - Xie, Guojin; Wu, Haiyan; Cai, Weiluo; Chen, Mo; Huang, Wending; Yan, Wangjun; Chang, Yong
Abstract : Neuroblastoma (NB) is an aggressive cancer that originates in the sympathetic nervous system and primarily affects children. Here, we show that high levels of RAD52 motif containing 1 (RDM1; a protein with similarities to RAD52, which is important for double‐strand DNA repair) are associated with poor clinical outcomes for NB. In addition, RDM1 −/− cells exhibited increased sensitivity to cisplatin, a common chemotherapy drug, and disruption of RDM1 suppressed NB cell proliferation. We also report that loss of RDM1 augmented cell apoptosis and induced cell cycle arrest, and that stable knockdown of RDM1 significantly inhibited NB tumor growth in a xenograft mouse model. Importantly, we identified that RDM1 promoted cell proliferation via the RAS–Raf–mitogen‐activated protein kinase kinase (MEK)–extracellular signal‐regulated kinase (ERK) signaling pathway. In conclusion, the current study demonstrates a correlation between DNA damage regulator RDM1 and the oncogenic RAS–Raf–MEK–ERK pathway in NB. Abstract : High RAD52 motif containing 1 (RDM1) levels are shown to be associated with poor clinical outcomes in neuroblastoma (NB). Disruption of RDM1 suppresses NB cell proliferation. RDM1 promotes cell proliferation via the RAS–Raf–MEK–ERK signaling pathway.